2x-4y = 3.8
3x - y = 17.7
multiply second equation by -4 so that when u add them both u will cancel the y's...
2x-4y = 3.8
-12x+4y = -70.8
now add them..
-10x = -67
x = 67/10 = 6.7
now plug this x in for any one of the original equations and solve for y....
2(6.7) - 4y = 3.8
13.4 - 4y = 3.8
-4y = -9.6
y = -9.6/-4 = 2.4
so the solution is (6.7,2.4)
2006-11-13 14:22:24
·
answer #1
·
answered by manish.narayan 3
·
1⤊
0⤋
2x - 4y = 3.8 --- 1st Equation
3x - y = 17.7 --- 2nd Equation
____________
2x - 4y = 3.8 --- X 3
3x - y = 17.7 --- X 2
_________________
6x - 12 y = 11.4
6x - 2y = 35.4
_________________
- 10 y = -24
y = -24/-10
y = 12 / 5
y = 2.4
Substitute y value in 2nd equation
3x - y = 17.7
3x - 2.4 = 17.7
3x = 17.7 + 2.4
3x = 20.1
x = 20.1 / 3
x = 6.7
x =6.7 and y = 2.4
2006-11-13 14:37:13
·
answer #2
·
answered by Muskaan 1
·
0⤊
0⤋
we could multiply -3x+y=7 by potential of three, so which you have -9x+3y=21. Then upload the two equations, canceling out y, giving you -7x=28, so x=28/-7= -4. SO, using first equation, the you be attentive to (2*-4)-3y=7, or -8-3y=7, or -3y=7+8=15, so y=15/-3= -5. So, x=-4 and y=-5.
2016-12-10 08:43:03
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
2x-4y = 3.8 & 3x-y= 17.7?
y=3x-17.7
then
2x-4(3x-17.7)= 3.8
10x + 4(17.7) =3.8
10x= 3.8 - 4(17.7)
x= 0.38 -4(1.77)
[
2006-11-13 14:20:51
·
answer #4
·
answered by Anonymous
·
2⤊
0⤋
2x - 4y = 3.8
2(x - 2y) = 3.8
x - 2y = 1.9
3x - y = 17.7
-y = -3x + 17.7
y = 3x - 17.7
x - 2(3x - 17.7) = 1.9
x - 6x + 35.4 = 1.9
-5x = -33.5
x = 6.7
y = 3(6.7) - 17.7
y = 20.1 - 17.7
y = 2.4
ANS : x = 6.7, y = 2.4
2006-11-13 14:22:50
·
answer #5
·
answered by Sherman81 6
·
0⤊
0⤋
solve for x of the first equation. plug it into the second equation to find y. take y and plug it into the first equation to find x.
2006-11-13 14:20:27
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
2x-4y=3.8 ---- (1)
3x-y=17.7 ---- (2)
From (2): 3x=17.7+y
x=(17.7+y)/3 ---- (3)
Substitute (3) into (1) : 2[(17.7+y)/3]-4y=3.8
----------------------------- (35.4+2y)/3 -4y = 3.8
----------------------------- 35.4+2y -12y = 11.4
----------------------------- 35.4-10y=11.4
----------------------------- 10y=24
----------------------------- y=2.4
Substitute y=2.4 into (1) : 2x-4(2.4)=3.8
------------------------------- 2x-9.6=3.8
------------------------------- 2x=13.4
------------------------------- x=6.7
Hence x=6.7,y=2.4.
2006-11-13 14:25:03
·
answer #7
·
answered by A 150 Days Of Flood 4
·
0⤊
0⤋